(untitled) (Journal of Pharma Insights and Research, 2025)
The emergence and spread of drug-resistant Candida albicans pose a significant clinical challenge, necessitating the development of novel therapeutic strategies. The combination of conventional antifungals with natural product-derived adjuvants represents a promising approach to overcome resistance and enhance therapeutic efficacy. Fungi of the genus Phellinus, particularly Phellinus igniarius, possess a long history of medicinal use in traditional systems and are recognized as a rich reservoir of bioactive molecules. This analysis consolidates and critically evaluates the preclinical evidence regarding the synergistic antifungal activity observed when fluconazole (FLC), a frontline azole, is combined with extracts of P. igniarius. In vitro studies consistently demonstrate that Phellinus extracts can significantly reduce the minimum inhibitory concentration (MIC) of FLC against both susceptible and, critically, multidrug-resistant strains of C. albicans. This synergistic interaction, quantitatively defined by a Fractional Inhibitory Concentration Index (FICI) < 0.5, is further validated in in vivo murine models of systemic candidiasis. These studies report that the combination therapy leads to markedly increased host survival rates and a significant reduction in fungal burden within target organs (e.g., kidneys, spleen) compared to FLC monotherapy. The primary mechanisms for this synergy are direct fungal membrane disruption by Phellinus-derived triterpenoids, potent inhibition of fungal efflux pumps (e.g., Cdr1p, Cdr2p) by specific phenolic compounds, and the profound anti-biofilm activity of the extract, which inhibits both formation and maturation. This multi-target effect effectively bypasses or neutralizes the primary FLC resistance mechanisms, restores FLC susceptibility, and suggests a viable strategy for treating recalcitrant fungal infections